Analisa Kinerja pada Standalone Server dan Clustering Server Teknologi RAC (Real Application Clustering) dengan Algoritma DNS (Domain Name System) Round Robin Berbasis Oracle Linux 6.4 di Lingkungan Virtual - Fauzi, Adnan (Jurnal Sistem Komputer, 2020)
ABSTRACT –A standalone server is a server that runs applications and databases on the same computer or server. As a service provider, the technology on the server is required to continue to develop in line with the needs. Therefore, a server clustering architecture was developed to serve the needs of clients on a larger scale. One solution to this problem is by implementing the RAC (Real Application Clustering) technology provided by Oracle 11gR2. RAC technology can fulfill client needs by using Round Robin DNS (Domain Name Server) algorithm. Then, this technology can help add new servers and recently assigned servers as cluster members. Also, RAC has advantages of memory storage for database storage. Based on the results of tests that have been done, server clustering has better quality according to a standalone server. Testing is done using QOS (Quality of Service) testing which is carried out on the network and also on load tests using TPM (Transaction per Minute) which is carried out on the database.